DIPLOMASI INDONESIA TERHADAP CHINA DALAM MENANGANI KASUS PENGANTIN PESANAN SEBAGAI BENTUK HUMAN TRAFFICKING TAHUN 2019 - Olivia Oktaviani (2021)
This study examines the diplomatic efforts carried out by Indonesia against China in 2019 in its efforts to overcome the case of ordered. This research uses diplomacy theory including humanitarian diplomacy and the concept of human trafficking and mail-order bride as a tool to analyze. The method used is descriptive analysis with a qualitative approach that describes the object or subject under study according to the data and information obtained for further analysis. Even though it had faced many obstacles, the success of diplomacy that has been carried out by Indonesia has made China finally open itself to equalize perspectives in looking at the mail-order bride case and accept the proposal submitted by the Indonesian Minister of Foreign Affairs in order to overcome and prevent the case of ordered bride from recurring. This is evidenced by the successful repatriation of 18 mail-order bride victims to Indonesia who had previously been detained at the Indonesian Embassy in Beijing. The Chinese government also approved the proposal regarding tightening the process of legalizing marriage documents between different nationalities, and was willing to cooperate to eradicate the mail-order bride chain by arresting agents operating in China.